CO-CREATION: WHY COOPERATION BETWEEN HEIS AND COMPANIES IS A PEDAGOGICAL TOOL IN TEACHING-LEARNING KNOWLEDGE TRANSFER PROCESSES - A CASE STUDY OF UNIVERSITY POLYTECHNIC OF PORTO - Rafael Pedrosa; Maria Teresa Pereira; Pilar Baylina (International Journal for Quality Research)
PORTO has been working on the Link ME UP - 1000 Ideas project for the past three years with the goal of implementing an innovative and pedagogical methodology that is based on the design thinking methodology. This work examines the co-creation axe's outcomes over six editions in terms of learning, expectations, and lessons to be improved. To solve a challenge, 48 teachers/facilitators were trained in the approach, 250 students took part in the development of competencies, and 48 projects were established and developed in collaboration with the participating organizations. The key findings are the following: the teachers'/facilitators' good integration of the new methodologies and tools used in this project and the opportunities this opens up for their classes; the companies' recognition of the project's added value and willingness to repeat the co-creation experience; and the students' increased development of soft skills and competencies.